Modular living wall system response to relative humidity and air temperature in Malaysia - Abd-Ghafar, Azmiah; Hashim, Mega Suria; Mohd-Fauzi, Amalina (Human Resource Management Academic Research Society, 2023)
The relative humidity is an essential environmental factor that affects thermal comfort. The influence of relative humidity on thermal comfort was studied in various mediums of green infrastructure. This environmental concern related to climate change pertains to the Sustainable Development Goals (SDGs) 13. A modular living wall system can be used as a climate mitigation measure to improve temperature at an outdoor building. Plants are the essential components of the system. The assessment of these experimental studies on modular living wall system, relative humidity, and air temperature is still scarce, especially from different plant species in tropical countries. As such, this study aimed to investigate the relationship between relative humidity and air temperature from the modular living wall system. This experimentation was undertaken in the industrial city of Pasir Gudang, Malaysia. Four plant species, Philodendron burle-marxii, Phyllanthus cochinchinensis, Nephrolepis exaltata, and Cordyline fructicosa ‘Miniature,’ were evaluated in 4-meter (width) x 1-meter (height). The study was conducted from January 1, 2019, to February 1, 2019. These results were evaluated by statistical analyses, which indicate that relative humidity significantly affects the thermal performance of the modular living wall system.